The Relationship Between Inter-Legality and Organized Social Processes in Land Formalization Practices in The Sovereignty-Contested Area of Tanintharyi Region, Myanmar - Ammarapala, Asis; Sanit, Peamsook (Nakhara : Journal of Environmental Design and Planning, 2023)
The study considers the Dawei Special Economic Zone (DSEZ) project, which was a land formalization case in a sovereignty-contested area conducted by de jure Myanmar state, de facto Karen Nation Union (KNU), and an international developer. The DSEZ project planning comprised deep-sea Ports, 250 sq. kms of industrial estate zone, and the two-lane 148 km road linking Dawei in Myanmar and Kanchanaburi Province of Thailand as its main features. Recent studies of Myanmar land institutions in sovereignty-contested areas have mainly discussed the factor of "inter-legality," the integration of non-state land laws, as the solution for land disputes between the central state and armed ethnic political groups. However, the real-world case in this study indicated a second factor, "organized social processes," working in correspondence with the first factor. This research paper explores how the two factors were used together the integration of customary land practice into statutory property institutions, influencing changes in the structure and process of land formalization practices, and illustrates the unclear property institutions of sovereignty-contested frontiers. This research paper is a single case study that benefited from the researcher's five years of work experience in the DSEZ project's design, planning, and land acquisition. The obtained information comprises the project's land formalization documentation, published land laws which were checked with the project manager using the triangulation method, and local newspaper clippings. The study concludes that inter-legality and organized social processes should be used together in practice planning to form more context-oriented land formalization practices, employing collective community memory to reduce institutional inertia. Furthermore, the mutually-agreed standards can help avoid direct power contestation between the de jure and de facto.